Formation of consolidated information resources of architectural organization - Kymytsia, Olha (Видавництво Львівської політехніки, 2016)
At this article the author considers the relevance consolidation information that provides various aspects of architecture and defines the main stages of the process consolidation information. Тhis paper contains the list of sources of consolidated information resource architectural organization and examples consolidated information products in the architectural activities.
Keywords: architectural organization; architectural activity; architectural decision; information; сonsolidation of information; communication; information resources